Arap Dili ve Belağatinde Kinâye - Özcan, Mehmet (My University, 2010)
Belâğat, Kinâye ÖZET ARAP DİLİ VE BELÂĞATİNDE KİNÂYE İnsanoğlunun, meramını durumun gerektirdiği şekilde kolay ve anlaşılır bir tarzda ifade etmesinin yanında muhataba tesir edecek tarzda söz söyleme sanatı olan belağat ilminin en önemli konusunu edebî sanatlar teşkil etmektedir. Arap Belâğatinde çok önemli bir yere sahip olan edebi sanatlardan biri de kuşkusuz kinâye sanatıdır. Çalışmamızda kinâye sanatı, daha iyi anlaşılabilmesi açısından kısımlara ayrılarak açıklanmış, kinâye konularıyla ilgili örnekler verilmiş ve bu örnekler, Kur’ân ayetleri ve Hz. Peygamberin hadisleriyle zenginleştirilmiştir. Ayrıca, kinâye sanatı ile ilgili Türk dili ve edebiyatından verdiğimiz örnekler hem bu sanatların anlaşılmasını kolaylaştırmış, hem de okuyucuya mukayese imkânı sağlamıştır. Key Words : Rhetoric, Allusion

ALLUSION IN THE ARABIC LANGUAGE AND RHETORIC Rhetoric, on the one hand, is the easy and understandable expression of the desires of human beings as the states of being require; on the other hand, it is the art of speech in the way to attract the people. The most important subject of rhetoric is the literary arts. One of the most important literary arts in the rhetoric of the Arabic language doubtlessly is the art of allegory. In our study, in order to better understand, the art of allegory is expressed after divisioning into parts and some examples of allegory are given. These examples are enhanced with verses from the Qur’an and the Prophet Mohammad’s sayings. Moreover, the examples of the art of allegory which we give from the Turkish language and literature both have made these arts to be betterunderstood; as well as have given the reader the opportunity to make comparisons.
Keywords: Arap Dili